Penegakan Hukum Terhadap Tindak Pidana di ZEE ( Zona Ekonomi Eksklusif Indonesia ) Konvensi Hukum Laut International (UNCLOS 1982) - Zainal Abidin Pakpahan; Marlon Simanjorang (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
Abstract: Exclusive Economic Zones (EEZs) and offshore seas are geographically difficult to monitor and enforce. Crimes such as illegal fish theft, piracy, and human trafficking are common in the region. This study aims to analyze the legal aspects and challenges in cracking down on criminal offenders operating in the EEZ and offshore seas. Through literature studies and case studies, this study highlights the importance of international cooperation, surveillance technology, and effective law enforcement to address these problems. Keywords: Criminal Acts, Indonesian EZZ